PENGARUH INTENSITAS ASET TETAP, TRANSAKSI HUBUNGAN ISTIMEWA, DAN BEBAN PAJAK TANGGUHAN TERHADAP PRAKTIK PENGHINDARAN PAJAK - Anjeng Sri Rukoyah; Adhitya Putri Pratiwi (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to determine the effect of fixed asset intensity, related party transaction, and deferred tax expense on tax avoidance practices. The population in this study were energy sector companies listed on the Indonesia Stock Exchange for the period 2019-2023 with a total sample of 11 companies for 5 years that met the predetermined criteria from a total of 90 companies and using a sampling technique, namely Purposive Sampling. The analysis used is multiple linear regression analysis and data processing is carried out with the help of Eviews 12 software. The results showed that simultaneously fixed asset intensity, related party transaction, and deferred tax expense affect tax avoidance practices. Partial research results show that fixed asset intensity has no effect on tax aggressiveness, special relationship transactions have no effect on tax avoidance practices, and deferred tax liabilities affect tax avoidance practices.